Analytics at Lie-Nielsen Toolworks: Custom-built Data Tools for a Unique Small Manufacturer. Issue 2 (November 2017) - Clark, Joseph Warren
Lie-Nielsen Toolworks (LNT) is a small, family-owned company manufacturing very-high-quality woodworking tools in coastal Maine. They face three major challenges: the sparse rural labor market makes it difficult to find and retain talent; their extreme quality standards lead to scrap and rework; they struggle to forecast demand and schedule production due in part to offering a large number of SKUs in small quantities. Having reorganized the factory layout and upgraded its CNC machines over the past two years, LNT is now turning to information systems and analytics as tools for improvement. Advised by an internal IT staff of one, an external ERP partner, and a consultant from the state university, Tom Lie-Nielsen must decide how to approach these information technologies, what benefits he can expect, and what organizational changes might be necessary to effectively leverage them.